Development of a module for cell culture based on a decellularized vascular tissue scaffold - Ataru , MURAHARA; Akimitsu , WAKIDA; Yu , MIYAKE; Shoichiro , TATEISHI; Takahiro , HIRAYAMA; Noor Azmi, Azran Azhim; Kazuaki , MURAMATSU; Masato , TANAKA; Osamu , ENDO; Kozo , MIYAZAKI; Hirotaka , MATSUO; Nariyoshi , SHINOMIYA; et al. (J-STAGE, 2011)
Decellularized tissues and organs have been intensively studied in order to use them as a scaffold for proliferation of recipient cells in tissue engineering/regenerative medicine applications. We established a fast and effective method for tissue decellularization by way of shaking a tissue in a detergent at 300 rpm. In addition, we developed a ring-clamp for fixation of decellularized tissue and created a scaffold module for cell culture by the combination of the ring-clamp and decellularized tissue. The module can be placed in a well of a commercially available 24-well plate. Smooth muscle cells that were seeded on a scaffold module consisting of a decellularized vessel and the ring-clamp showed proliferation with a spindle shape similar to that of vascular smooth muscle cells in the biological body. Vascular endothelial cells that adhered to the scaffold module showed enhanced susceptibility to histamine-induced Ca2+ influx.